PERSONALITY FACTORS AS A MEDIATOR IN THE RELATIONSHIP BETWEEN HAPPINESS AND PSYCHOLOGICAL WELL-BEING: A PARALLEL MEDIATION MODEL - Khan , Hina Hafiz; Pathan, Shafiq Yusufkhan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Psychological well-being influences every aspect of an individual's behaviours, thus it's important to understand how happiness and traits affect psychological well-being. This study aimed to investigate the relationship between happiness and psychological well-being, mediated by personality factors. 260 young adults aged 17–39 were surveyed in order to administer Ryff's psychological wellbeing scale, Lyubomirsky's subjective happiness scale, and Rammstedt's Big Five personality inventory. The findings demonstrate that psychological well-being and extraversion factor have a significant effect on inhabitants and that psychological well-being has a significant relationship with happiness. Extraversion, agreeableness, and openness to experience mediated psychological well-being and happiness relationships.